Isolation of bifunctional reactive dye hyrolysis compounds - (:unkn) unknown (My University, 1996)
The bifunctional reactive dye Sumifix Supra Blue BRF from Sumitomo has two different reactive groups: monochlorotriazine and sulphatoethylsulphone. Several hydrolysis products are produced during dyeing and have been isolated by being first removed from the salt by dialysis and thin-layer chromatography. The final purification is also done by thin-layer chromatography. Three main hydrolysis products are obtained and their infrared spectra are determined.